Impact of rapid centrifugation on routine coagulation assays in South Africa - Reola Haripersadh; Dashini Pillay; Nadine Rapiti (AOSIS, 2022)
Background: The recommendation for coagulation blood samples is to centrifuge at 4000 revolutions per minute (rpm) for 15 min to produce platelet-poor plasma before analysis. Rapid centrifugation, defined as centrifuging samples at higher speeds for shorter durations, could potentially reduce turn-around times (TAT), provided sample integrity is maintained. Objective: This study assessed the impact of rapid centrifugation on routine coagulation assay results. Methods: Blood samples were collected from volunteers at Inkosi Albert Luthuli Central Hospital and King Edward VIII Hospital, Durban, KwaZulu-Natal, South Africa, from September to November 2021. Samples were centrifuged using Method A, the current standard (4000 rpm/15 min), Method B (4000 rpm/10 min), Method C (5000 rpm/10 min) and Method D (5000 rpm/5 min). Platelet count, prothrombin time, activated partial thromboplastin time, thrombin time (TT), fibrinogen and D-dimer levels were analysed and results from Methods B, C and D compared to reference Method A. Results: Platelet-poor plasma was obtained from all samples (n = 60) using Methods A and B, and from 33/60 (55%) samples using Methods C and D. Differences between Method A and Methods C and D for normal prothrombin time, normal D-dimer and abnormal TT results were statistically significant. Prothrombin time results correlated strongly across all methods, while TT and D-dimer results correlated poorly. Activated partial thromboplastin time and fibrinogen results showed no significant differences across all methods. Conclusion: Rapid centrifugation at 4000 rpm/10 min (Method B) showed results consistent with the reference method. This method could potentially reduce the overall TAT for routine coagulation assays.